Evaluation of the Relationship between Ossification of Sternal Joints and Age with Multi-Slice CT Scan - Gokhan Gokalp; Selman Candan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: Sternum radiograph is used in determination of age after 21 years old according to manubriosternalbody (MB) and xiphisternal joint body (XB) ossification. In this study, we intend to estimate age usingmulti-slice CT images as radiographs have lower sensitivity and CT images demonstrate ossification better.Materials and Methods: Multi-slice thorax CT images found in PACS archive are evaluated retrospectively.Cases between 21-65 years old are selected. Coronal reconstruction images were obtained. MB and XB jointossification presence and degree are evaluated in respective age groups. MB joint ossification is gradedas 0-3 and XB joint ossification graded as 0-1. Relation between variables is examined with Spearmancorrelation coefficient. Threshold for age variable is calculated using ROC analysis.Results: Multi-slice CT images of 396 cases are examined (198 females, 198 males). In females and males,MB and XB fusion was seen to start between age group of 21-25 years but there were complete fusion ina few. In 61-65 age groups there were cases without complete fusion. There was statistically significantdifference in males and females according to MB and XB joint ossification in between age groups (p<0.001).Conclution: Evaluation of MB and XB joint ossification with CT scan in age estimation is not appropriatebetween wide age groups.